Definition of a particularly vulnerable consumer under Directive 2005/29/EC on unfair commercial practices - Ondrejová, Dana (Review of European and Comparative Law, 2025)
Directive 2005/29/EC on unfair commercial practices establishes the normative benchmark of the “average consumer” as the primary standard for assessing the legality of commercial conduct. However, Article 5(3) of the Directive introduces an important corrective mechanism by recognizing the category of the “particularly vulnerable consumer,” whose economic behavior may be disproportionately influenced by age, mental or physical frailty, or credulity. This article analyzes the legal contours of this category, with particular regard to the jurisprudence of the Court of Justice of the European Union and Czech judicial practice. The article examines both endogenous forms of vulnerability (such as illness, disability, or old age) and exogenous or situational factors (including linguistic barriers, lack of digital literacy, or acute distress), emphasizing the requirement of an objective and generalized assessment. Special attention is devoted to the cumulative conditions for the application of Article 5(3), notably the existence of a clearly identifiable group, the substantial distortion of economic behavior, and the criterion of reasonable foreseeability on the part of the trader. The article concludes that the concept of the particularly vulnerable consumer functions as a necessary complement to the average consumer model, thereby aligning EU consumer law more closely with social reality while preserving a fair balance between legitimate commercial practices and effective consumer protection.